Negative Pore Water Pressure in Aquitard Enhances Land Subsidence: Field, Laboratory, and Numerical Evidence. Issue 1 (27th December 2021) - Liu, Chun; Shi, Bin; Gu, Kai; Zhang, Tiansheng; Tang, Chaosheng; Wang, Yue; Liu, Suping
Abstract: Land subsidence in the south Yangtze River delta area did not cease when the ground water table has risen during the last 20 years. This issue was generally interpreted as a result of the slow release of excess pore water pressure in the aquitards and the creep of soil. Recent distributed strain monitoring data in boreholes shows a great compressive strain in the aquitard above the main exploited aquifer. In laboratory tests, such great compressive strain also is observed in the clay layer during the draining of the underlying sand layer. Furthermore, a negative pore water pressure is observed in the clay layer, which significantly correlates with the change of the compressive strain. An improved discrete element model was used to simulate the deformation of soil layers under the effect of the negative pressure. The simulation results coincide with the tests, and the negative pressure enhances the compression of aquitard. Due to the effect of the negative pore water pressure, aquitards may be compressed during the draining and recharging cycles in the south Yangtze River delta area. Key Points: The monitoring data of the Yangtze River delta show a great compressive strain in the clay Negative pore water pressure was observed in laboratory tests and it contributes to the compression of soil The results simulated by an improved discrete element model correspond with the tests and field observation